ETHNIC HISTORY AND GEOGRAPHICAL LOCATION OF TURKIC PEOPLES IN SOUTHERN UZBEKISTAN - Vahidov Sukhrobjon Olimjonovich (Western European Studies, 2025)
The article examines the ethnic history and geographical location of Turkic peoples in Southern Uzbekistan. wide coverage. The article covers the national ethnic culture and origin of groups related to the origin of the Turkic peoples in our country, as well as the evolutionary details of their formation into a single ethnic elite.
Keywords: Byzantium; Altai; Turkish